Thinking with Stories: A Renewed Call for Narrative Inquiry as a Social Work Epistemology and Methodology - Shaw, Jessica (Canadian Social Work Review / Revue canadienne de service social, 2017)
As a relational epistemology and research methodology, narrative inquiry is one way that people come to know experience through story. Social workers are experienced in working with people’s stories, yet there is a dearth of literature where both social work and narrative inquiry are discussed alongside each other. This paper highlights the particular ways that a researcher commits to living and understanding a narrative view of experience as they engage in research that is relational. It explains some of the language that narrative inquirers use to describe their work, and uses examples from a social work doctoral dissertation to demonstrate the methodological touchstones of a social work narrative inquiry. It concludes with an invitation for social workers to consider narrative inquiry as a process that can guide and advance both clinical practice and social justice work.